Determination of Corporate Action Announcement and Market Reaction: : Stock Price and Stock Liquidity Before and Afte - Jeli Nata Liyas; Fajri Adrianto (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
This study aims to determine the effect of market reaction in corporate action announcements on stock prices and stock liquidity. This study uses qualitative methods and literature research with reference to the latest journals published by scholars and examines literature books based on the theories discussed, especially in the context of financial management. The results of this study will build a research hypothesis which will be developed in further research by the author. The findings of this study will be continued with data collection and hypothesis testing. Stock data will be taken on stocks listed on the Indonesia Stock Exchange using a purposive sample selection method. It is planned that this study will test the hypothesis using SEM AMOS software version 24 and SPSS Versti 26 to process and screen data. Research will have an impact on increasing understanding for investors who will invest in the Indonesia Stock Exchange.